Measurement and ab initio Investigation of Structural, Electronic, Optical, and Mechanical Properties of Sputtered Aluminum Nitride Thin Films - Alsaad, A. M.; Al-Bataineh, Qais M.; Qattan, I. A.; Ahmad, Ahmad A.; Ababneh, A.; Albataineh, Zaid; Aljarrah, Ihsan A.; Telfah, Ahmad (Frontiers in physics, 2020)
We report our results on highly textured aluminum nitride (AlN) thin films deposited on glass substrates, oriented along the c-axis, using DC-magnetron sputtering technique for different values of back pressure. The structural, electronic, optical, piezoelectric, dielectric, and elastic properties of sputtered AlN thin films are measured and characterized. In particular, X-ray powder diffraction (XRD) technique shows that AlN thin films exhibit a hexagonal structure. Moreover, we employed ab initio simulations of AlN using the Vienna Ab Initio Simulation Package (VASP) to investigate the structural and the electronic properties of hexagonal AlN structures. The experimental lattice parameters of the as-prepared thin films agree well with those calculated using the total energy minimization approach. The optical parameters of AlN thin films, such as transmittance and refractive index, were measured using UV–vis measurements. Our measurements of refractive index, n, of AlN thin films yield a value of 2.2. Furthermore, the elastic, piezoelectric, and dielectric tensors of AlN crystal are calculated using VASP. The dynamical Born effective charge tensor is reported for all atoms in the unit cell of AlN. Interestingly, ab initio simulations indicate that AlN has a static dielectric constant approximately equal to 4.68, which is in good agreement with the reported experimental value. In addition, the clamped-ion piezoelectric tensor is calculated. The diagonal components of the piezoelectric tensor are found to be e33=1.79 C/m2 and e31=-0.80 C/m2. The large values of the piezoelectric coefficients show that a polar AlN crystal exhibits a strong microwave piezoelectric effect. Additionally, the components of the elastic moduli tensor are calculated. The extraordinary electronic, optical, piezoelectric, and elastic properties make AlN thin films potential candidates for several optoelectronic, elastic, dielectric, and piezoelectric applications.